FROM ORGANIC SOIL TO PLATE: THE ROLE OF ECO-FARMING IN FOOD SECURITY - Loso Judijanto (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Eco-agriculture plays a vital role in supporting global food security through approaches that maintain ecological balance and long-term sustainability. By implementing agricultural practices such as the use of organic fertilisers, crop rotation and natural pest control, soil quality and natural resources are maintained and enhanced, which in turn increases agricultural productivity. In addition, eco-agriculture contributes to the well- being of farmers and rural communities by diversifying farming practices that increase income and access to resources. Collaboration among stakeholders, including governments, research institutions, the private sector and communities, is essential to foster the adoption of innovative technologies and supportive policies, thereby creating a more efficient and equitable food system. Eco-agriculture offers a potential solution to achieve agricultural sector sustainability and global food security.